2017
DOI: 10.1177/0194599817717662
|View full text |Cite
|
Sign up to set email alerts
|

What Do Patients Want from Otolaryngologists? A Discrete Choice Experiment

Abstract: Objectives Patient preferences are crucial for the delivery of patient-centered care. Discrete choice experiments (DCEs) are an emerging quantitative methodology used for understanding these preferences. In this study, we employed DCE techniques to understand the preferences of patients presenting for an ear, nose, and throat clinic visit. Study Design DCE. Setting Decision science laboratory. Methods A DCE survey of 5 attributes-wait time, physician experience, physician personality, utilization of visit time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
(42 reference statements)
0
10
2
Order By: Relevance
“…In otolaryngology, a field often dedicated to delivering quality‐of‐life interventions, it is particularly prudent to understand the individuals’ underlying valuations and preferences. Unfortunately, providers too often lack awareness of such values . This study helps delineate how the general public views the condition of dysphonia, evidence that may contribute toward measuring value in otolaryngology.…”
Section: Discussionmentioning
confidence: 99%
“…In otolaryngology, a field often dedicated to delivering quality‐of‐life interventions, it is particularly prudent to understand the individuals’ underlying valuations and preferences. Unfortunately, providers too often lack awareness of such values . This study helps delineate how the general public views the condition of dysphonia, evidence that may contribute toward measuring value in otolaryngology.…”
Section: Discussionmentioning
confidence: 99%
“…Eight additional studies assessed understanding in both pretesting and within the DCE survey [43,[85][86][87][88][89][90][91]. These studies were similar to the other reported studies, with pretesting results used to refine the wording and formatting of the surveys, and the rationality tests using dominant or repeated choice tests and debriefing questions.…”
Section: Pilot Testingmentioning
confidence: 83%
“…Patient preference research continues to gain importance in otolaryngology and medicine at large . Along with other preference assessment methodologies, prospective assessment of health state utility values contributes both to a patient‐centric understanding of the disability resulting from voice disorders, and helps inform the economic evaluation of our interventions for the purpose of resource allocation at a societal level.…”
Section: Discussionmentioning
confidence: 99%